Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Kompetensi Pedagogik Guru Di SD Negeri Kecamatan Margadana Kota Tegal - Jayanti, Rowi; Yuliejantiningsih, Yovitha; Prayito, Muhammad (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study analyzes the influence of academic supervision of school principals on the pedagogic competence of teachers at SDN Margadana Tegal. Pedagogic competence is focused on the teacher's ability to design, implement, assess, and evaluate learning. The background of the research is based on the low pedagogic competence of teachers identified through initial observation. Teachers still experience obstacles in the preparation of learning tools, the implementation of learning is not as planned, and has limitations in classroom management and the use of teaching aids. The 2024 Teacher Performance Assessment (PKG) shows pedagogic competence as the lowest competence. Education Report Data supports these findings with a decrease in achievement from the "Good" category to "Adequate" in 2024. This condition states that teachers' pedagogic competence must be improved, one of which is through academic supervision. The approach used is quantitative correlational design which involved 205 teachers, and a randomly selected sample of 134 teachers. Descriptive data analysis, correlation coefficient, determination coefficient, and regression analysis to collect data, which were distributed through questionnaires. Test prerequisites such as normality, linearity, and multicollinearity. The findings of the study stated that the academic supervision of the principal affects pedagogic abilities. This is indicated by the f-value of 392.717 > f table 3.91, the Sig value of 0.000 < 0.05, the contribution of 74.8% for the medium category. The correlation between the academic supervision of the principal and the pedagogic competence of the teacher is 0.865 in the very strong category. These results indicate that there is a very significant relationship between the academic supervision of the principal and the pedagogic competence of the teacher. For the value of the constant coefficient is 24.215, the coefficient of the academic supervision variable is 0.876. The results of this study show that the better the academic supervision of the principal contributes to the improvement of teachers' pedagogic competence.